Light-stimulated smart thermo-responsive constructs for enhanced wound healing: A streamlined command approach - Bingcheng Yi; Lei Yu; Yating Yang; Carlos F. Guimarães; Ruijie Xu; Thavasyappan Thambi; Boya Zhou; Qihui Zhou; Rui L. Reis (Asian Journal of Pharmaceutical Sciences, 2025)
Efficient reconstruction of severe cutaneous wounds necessitates the orchestration of effective cell-mediated matrix remodeling and robust protection against microbial invasion. Herein, we engineered a near-infrared light (NIR)-stimulated, thermo-responsive bilayer system based on a drug-loaded hydrogel with a thermal-responsive temperature of ∼42 °C as the matrix layer and an antibacterial nanofibrous mat as the top layer. The matrix layer integrates basic fibroblast growth factor (bFGF)-loaded thermosensitive gelatin (Gel) hydrogel with polydopamine-Cu2+ coated short nanofibers (P@SF). Upon NIR exposure, P@SF elicits a photothermal effect, causing a rapid increase in temperature by 13.4 °C within 1 min at a power density of 0.75 W/cm2, which triggers the gel-sol transition of Gel and controls the release of bFGF. This, in turn, enhances fibroblast and endothelial cells ingrowth into the hydrogel, fostering cell functionalization and matrix remodeling. The top layer consists of poly(L-lactide-co-caprolactone) nanofibers functionalized with lysine-doped polydopamine and poly-l-lysine. It possesses antibacterial efficacy by isolating, controlling (76.23% for E. coli and 89.16% for S. aureus), and eliminating bacteria upon NIR activation. In rat skin wound models, this NIR-responsive smart bilayer system prevents S. aureus-mediated bacterial infection (indicative of reduced IL-6 expression), regulates CD31-positive neovascularization, and facilitates collagen remodeling for skin regeneration. In summary, this study introduces a novel strategy, inspired by the centralization of authority, for developing a smart thermo-responsive system with promising potential for the effective reconstruction of severe cutaneous wounds.